Enterobactin and salmochelin S4 inhibit the growth of Staphylococcus aureus - Davidov, Yaacov; Tejman-Yarden, Noa; Robinson, Ari; Rahav, Galia; Nissan, Israel (Frontiers in Cellular and Infection Microbiology, 2025)
There is increasing demand for novel antimicrobial agents to tackle the antimicrobial resistance crisis. Here we report that two Enterobacteriaceae-produced siderophores, enterobactin and salmochelin S4, inhibit the growth of Staphylococcus aureus isolates, including methicillin-resistance S. aureus (MRSA) clinical isolates. The IC50 for different S. aureus isolates were 2-5 µM for salmochelin S4 and 5-10 µM for enterobactin. This inhibitory activity was partially repressed by adding Fe+3. These siderophores also inhibited the growth of Enterococcus strains, including vancomycin-resistant enterococci (VRE) clinical isolates, though less effectively than for S. aureus. The growth of various Gram-negative bacteria was barely affected by these siderophores. These results shed new light on the role of enterobactin and salmochelin in bacterial physiology and ecology and have potential for the development of novel strategies to combat the rapid rise of multidrug-resistant bacteria.